2015
DOI: 10.1183/13993003.00635-2015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of airflow limitation in subjects 65–100 years of age

Abstract: The true incidence of chronic obstructive pulmonary disease is largely unknown, because the few longitudinal studies performed have used diagnostic criteria no longer recommended by either the European Respiratory Society or the American Thoracic Society (ATS).We studied the incidence and significance of airflow limitation in a population-based geriatric sample using both an age-dependent predicted lower limit of normal (LLN) value and a fixed-ratio spirometric criterion.Out of 2025 subjects with acceptable sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
4
39
3
2
Order By: Relevance
“…)", as well as those studies that compare outcomes among individuals diagnosed with chronic obstructive pulmonary disease (COPD) on the basis of the fixed ratio versus lower limit of normal (LLN) thresholds. In this issue of the European Respiratory Journal (ERJ), LUOTO et al [2] report the results of a study that fulfils both goals.…”
Section: @Erspublicationsmentioning
confidence: 95%
See 3 more Smart Citations
“…)", as well as those studies that compare outcomes among individuals diagnosed with chronic obstructive pulmonary disease (COPD) on the basis of the fixed ratio versus lower limit of normal (LLN) thresholds. In this issue of the European Respiratory Journal (ERJ), LUOTO et al [2] report the results of a study that fulfils both goals.…”
Section: @Erspublicationsmentioning
confidence: 95%
“…As reviewed by LUOTO et al [2], there were few studies quantifying the incidence of spirometrically confirmed COPD in the literature, particularly within the elderly. As exemplified in their table 5, there is a wide heterogeneity in the published estimates of incidence, varying by method, location, age and sex.…”
Section: @Erspublicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also abundant evidence that this reduction is most accurately identified as an individual value less than the lower limit of the normal range (LLN) specific to that individual, as determined from an appropriate healthy, non-smoking, reference population [1]. Because the FEV1/FVC ratio declines normally with age, using a non-individualised cut-off, such as 0.70, has been shown to cause an unacceptable level of misclassification with age and sex bias; this leads to over-diagnosis of 30% or more of older men and under-diagnosis of younger women [2][3][4][5]. There is much less consensus, however, on methods to indicate disease severity or to assess the likelihood of future outcomes.…”
mentioning
confidence: 99%